Hubungan antara Motivasi Menghafal Al-Qur'an dan Prestasi Akademik Mahasiswa Pendidikan Agama Islam di Universitas Al-Azhar Indonesia - Muklis, Abdul Hafiz Muhamad; Muchlis, Madian; Yanti, Ili (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
Memorizing the Qur'an can enhance intellectual and spiritual intelligence. This activity involves mental aspects, which are influenced by motivation. Therefore, this study aims to determine the correlation score between students' motivation in memorizing the Qur'an and their academic performance in the Tahfidz Al-Qur'an course. The research method is descriptive quantitative using SPSS analysis. The sample selection used purposive sampling, where the sample consisted of 19 students who are Qur'an memorizers (hafidz). Data collection methods included a questionnaire on motivation for memorizing the Qur'an and learning outcomes in the Tahfidz Al-Qur'an course. The results showed that (1) From 19 students who completed the questionnaire, the mean value was 54.53, (2) The average score of assignments, midterm, and final exams in the Tahfidz Al-Qur'an course showed an average value of 82.58, (3) The hypothesis test results from Pearson correlation test showed a significance value of 0.000 < 0.05 with a Pearson correlation value of 0.977, indicating a perfect correlation, and simple linear regression test showed a significance level of 0.000 < 0.05, with F-value = 354.812, and R square value showing a score of 0.954. This means there is an influence of Tahfidz Al-Qur'an Motivation on Student Achievement variable of 95.4%.Keyword - Motivation, Student Achievement, Tahfidz Al-Qur'an.